Post-Traumatic Stress Disorder in Film and Media - Lee, Jason. author. aut Link
X, 222 p.
Keywords: "Film and media can traumatise as much as capture the play and fallout of the unbearable in human life. In this excellent book, Jason Lee removes the popcorn and provides a sobering account of PTSD in our rapidly changing digital world. In all, a lively and sobering account of the interface between screens and PTSD, and the impact on our experiences and memories." —Professor Paul Crawford, The University of Nottingham, UK. This book expounds how post-traumatic stress disorder (PTSD) became so ubiquitous. The relationships between trauma, memory, and media, including the cultural, psychological, and social dimensions of PTSD are analysed. This work provides an examination of PTSD across diverse cultural contexts, shedding light on its profound impact on human experience and societal structures. This work addresses the role of social media internationally, the pornography industry, and conspiracy theories, in perpetuating trauma and shaping societal attitudes. From feature films, including Apocalypse Now, The Deer Hunter, and Jacob’s Ladder, to hit television shows such as the BBC’s Bodyguard, visual cultures have been instrumental in popularizing an understanding of PTSD. Often these are traditional “triumph over adversity” narratives. In others what is relevant is the wider postwar political landscape. Controversial wars have led to mental health problems for returning soldiers, depicted as part of a metaphoric wound for a nation. At its heart, America is concerned with the survival of the fittest, a Social Darwinist creed fused with manifest destiny and turbo capitalism. Any weaknesses, such as mental problems including PTSD, contradicted and challenged the essence of the pioneering American spirit. A book on PTSD at this moment is necessary, as the subject has become popularized and politicized, just as “madness” became a term to define an era. Through advocating for interdisciplinary approaches to foster healthier perspectives and support, here we come to a deeper understanding of how digital cultures have impacted the politics of time and memory. Professor Jason Lee is a Chartered Psychologist, elected Fellow of the Royal Historical Society, and Professor of Film, Media and Culture at De Montfort University, Leicester. The author/editor of 20 books, these include Culture, Madness and Wellbeing: Beyond the Sociology of Insanity (Springer 2023), Sex Robots: The Future of Desire (Palgrave 2017), and Nazism and Neo-Nazism in Film and Media (2018).